2015
DOI: 10.1007/s00415-015-7985-z
|View full text |Cite
|
Sign up to set email alerts
|

NEFL N98S mutation: another cause of dominant intermediate Charcot–Marie–Tooth disease with heterogeneous early-onset phenotype

Abstract: The purpose of this study was to describe a pedigree with NEFL N98S mutation associated with a dominant intermediate Charcot-Marie-Tooth disease (DI-CMT) and heterogeneous early-onset phenotype. The pedigree comprised two patients, the proband and her son, aged 38 and 5 years. The proband, evaluated at age 31, showed delayed motor milestones that, as of the second decade, evolved into severe phenotype consisting of sensorimotor neuropathy, pes cavus, clawing hands, gait and kinetic cerebellar ataxia, nystagmus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
0
24
1
1
Order By: Relevance
“…A 6-year-old boy inherited a heterozygous N98S mutation from his affected mother [2]. However, in contrast to our study, the boy reported by Berciano et al was mildly affected and the atrophy in the proband only affected cerebellum but not spinal cord.…”
Section: Discussioncontrasting
confidence: 94%
“…A 6-year-old boy inherited a heterozygous N98S mutation from his affected mother [2]. However, in contrast to our study, the boy reported by Berciano et al was mildly affected and the atrophy in the proband only affected cerebellum but not spinal cord.…”
Section: Discussioncontrasting
confidence: 94%
“…Although only 5 out of 14 patients conformed to the full syndrome, its recognition may aid in the differential diagnosis with other autosomal recessive cerebellar ataxias. 18 Of note, NFL E90K or N98S mutants share a particular phenotype in vitro, different from that observed with substitutions of amino acid P8, 50 and Nefl N98S/+ mice display an earlyonset phenotype with tremor and pathological changes in the CNS including neurofilament aggregates in the spinal cord and cerebellum. 56 Beyond the above genotype-phenotype associations, identification of uncommon clinical features such as hearing loss, pyramidal tract signs or ataxia may be useful in the differential diagnosis of NEFL-related CMT with other forms of CMT (see online supplementary table 5).…”
Section: Neuromuscularmentioning
confidence: 92%
“…Twenty-four mutations were clustered in six regions of the NFL polypeptide (figure 4): the initial segment of the head domain (amino acid positions [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], the junction between the head and the rod domains (90-98), coil 2A (265-268), the mid portion of coil 2B (311-336), the end portion of coil 2B (384-396) and the tail subdomain A (421-440). Mutations in the head domain and the two ends of the rod domain accounted for 75% of kindreds and four common mutations within these regions (P8R, P22S, N98S and E396K) were observed in 55% of kindreds.…”
Section: Neuromuscularmentioning
confidence: 99%
See 2 more Smart Citations